Malnutrition and its associated factors among children in Murree, Rawalpindi - Khan, Shahrukh; Nazir, Aqsa; Shehzad, Amna; Abid, Junaid; Qaiser, Ameena; Khan, Tayyab Mumtaz (International Journal Of Community Medicine And Public Health, 2022)
Background: Malnutrition is one of the main health issues among children. Malnutrition is more prevalent in developing countries. Malnutrition among children is affected by many factors. These factors are studied in many parts of the world but they are understudied in most the areas of Pakistan. This study aimed to assess the incidence of malnutrition and its associated factors among children in Murree, Rawalpindi, Pakistan. Methods: This descriptive cross-sectional study was carried out among children of Murree, Rawalpindi for about 6 months from August 2021 to January 2022. Simple random sampling along with an established inclusion and exclusion criteria was applied to enroll 316 participants. A self-adapted questionnaire was applied to take data after taking ethical approval from the institutional research board and informed consent from the participants. Results: The incidence of underweight, normal weight, overweight and obesity among school children of study population was 22.80%, 35.40%, 26.90%, and 14.90% respectively. The association between malnutrition and gender (p=0.001), birth weight (p=0.01), supplementation intake (p=0.03), filtered water use (p=0.02), hygiene (p=0.01), vaccination status (p=0.04), recurrent infection history (p=0.02), socioeconomic status (p=0.04), mother education (p=0.04), mother occupation (p=0.03), awareness of parents about balanced diet (p=0.02), and family size (p=0.04) was statistically significant, whereas association between nutritional status and age group (p=0.05) was insignificant. Conclusions: The incidence of underweight, overweight, and obesity was remarkable among children. Many factors such as gender, birth weight, supplementation intake, filtered water use, hygiene, vaccination status, recurrent infection, socioeconomic status, mother education, mother occupation, parental awareness about a balanced diet, and family size were found to associate with malnutrition among children.